2011
DOI: 10.1111/j.1469-1809.2011.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of COL1A1 and TGFB1 Polymorphisms with Otosclerosis in a Tunisian Population

Abstract: SummaryOtosclerosis is a condition characterized by an abnormal bone metabolism in the otic capsule, resulting in conductive and/or sensorineural hearing loss. Otosclerosis is a common disorder in which genes play an important role. Case-control association studies have implicated several genes in the abnormal bone metabolism associated with otosclerosis: COL1A1, TGFB1, BMP2, and BMP4. To investigate the association of these genes with otosclerosis in the Tunisian population, we examined nine single nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 31 publications
0
51
1
7
Order By: Relevance
“…Scanning these loci has not identified any causative genes to date. In parallel, genetic association studies were carried out and showed the association of OTSC with polymorphisms in the COL1A1, TGFB1, BMP2, BMP4, and RELN genes in multiple populations (McKenna et al, 1998;Thys et al, 2007a;Schrauwen et al, 2008;Schrauwen et al, 2009;Khalfallah et al, 2010;Khalfallah et al, 2011;Priyadarshi et al, 2013). Gene expression profiling of disease tissue compared to controls has been suggested as a method to investigate the genetic basis of complex disorders (Xiong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning these loci has not identified any causative genes to date. In parallel, genetic association studies were carried out and showed the association of OTSC with polymorphisms in the COL1A1, TGFB1, BMP2, BMP4, and RELN genes in multiple populations (McKenna et al, 1998;Thys et al, 2007a;Schrauwen et al, 2008;Schrauwen et al, 2009;Khalfallah et al, 2010;Khalfallah et al, 2011;Priyadarshi et al, 2013). Gene expression profiling of disease tissue compared to controls has been suggested as a method to investigate the genetic basis of complex disorders (Xiong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several association studies have been performed to determine the genetic contributors for sporadic forms of OTSC. These studies have shown the association of OTSC with polymorphisms in the COL1A1 (MIM 120150), TGFB1 (MIM 190180), BMP2 (MIM 112261), BMP4 (MIM 112262), and RELN (MIM 600514) genes (McKenna et al, 1998;Thys et al, 2007a;Schrauwen et al, 2008;Schrauwen et al, 2009;Khalfallah et al, 2010;Khalfallah et al, 2011;Priyadarshi et al, 2013;Ealy et al, 2014). Some of the studies failed to replicate these associations due to small sample size or different ethnicity (Tshifularo & Joseph, 2008;Priyadarshi et al, 2010;Iossa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of candidate genes through genetic association studies is the method of choice for investigating the genetic basis of complex traits, and replication of these findings is essential for establishing the credibility of such results. In this replication study, a comprehensive investigation of TGFB1 polymorphisms was rigorously done to evaluate the positive findings from previous reports . TGFB1 plays an important role in cell growth and differentiation in a wide variety of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Several common polymorphisms in the TGFB1 gene with possible functional significance in the regulation of transcriptional activity have been reported. An association of TGFB1 polymorphism c.788C > T has been investigated with OTSC . The functional analysis has shown a higher activity of the causative allele c.788T than the wild‐type allele .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation